2010
DOI: 10.1111/j.1365-2648.2010.05295.x
|View full text |Cite
|
Sign up to set email alerts
|

Living alone with dementia: an interpretive phenomenological study with older women

Abstract: Insight into the impact of past experience with others with dementia could inform nursing assessment and advocacy for health/social services that are sensitive to the potential emotional impact of mixing people with varied levels of dementia in the same programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 37 publications
4
54
0
Order By: Relevance
“…It was interesting that 2 of the women had family members present at their request, supporting findings [11,21] in the literature regarding the importance of the family to many people with dementia.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It was interesting that 2 of the women had family members present at their request, supporting findings [11,21] in the literature regarding the importance of the family to many people with dementia.…”
Section: Discussionsupporting
confidence: 69%
“…Phenomenology focuses on increasing the understanding of the perspective of the lived experience of research participants and can serve to assist nurses to campaign for effective services [11] . The philosophical ideas of Heidegger and Husserl underpin the phenomenological approach to enquiry [12] which can be either descriptive or interpretive.…”
Section: Methodsmentioning
confidence: 99%
“…These risks threaten autonomy. De Witt et al [35] found that people with dementia of mild and moderate degree had risk awareness and acknowledged their limited time for living at home. They wished to postpone the time for moving to an institution for as long as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In maintaining their lives at home, our participants demonstrated resilience and ability, and like frailer people more generally, ‘balance[d] loss and capacity in their everyday lives’ [45]. Participants expressed the hope that they would remain as they were, linking with De Witt et al’s [46] concept of people with dementia ‘holding back time’. The view that ‘anyone can fall’ or suffer an accident, minimises the link to personal vulnerability [18].…”
Section: Discussionmentioning
confidence: 77%